2006
DOI: 10.1111/j.1365-2141.2006.06419.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome after relapse in children with acute myeloid leukaemia

Abstract: Summary In the Nordic Society for Paediatric Haematology and Oncology paediatric study acute myeloid leukaemia (AML) 93, event‐free survival was 50% and overall survival was 66%, indicating that many patients were cured following relapse. Factors influencing outcome in children with relapsed AML were investigated. The study included all 146 children in the Nordic countries diagnosed with AML between 1988 and 2003, who relapsed. Data on disease characteristics and relapse treatment were related to outcome. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
100
6
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(124 citation statements)
references
References 20 publications
17
100
6
1
Order By: Relevance
“…Comparable observations have been reported by other groups: A 3-year OS rate of 24% after relapse was reported for treated and untreated pediatric patients from the MRC (Medical Research Council) AML10 trial. 6 The 5-year OS was 34% in 146 patients from the NOPHO (Nordic Society for Pediatric Hematology and Oncology) studies 9 and 33% in 106 patients treated within the French LAME (Leucémie Aiguë Myéloblas-tique Enfant) 89/91 protocol. 3 Data from the St Jude institutional trials showed a 5-year OS of 23% in 160 relapse patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable observations have been reported by other groups: A 3-year OS rate of 24% after relapse was reported for treated and untreated pediatric patients from the MRC (Medical Research Council) AML10 trial. 6 The 5-year OS was 34% in 146 patients from the NOPHO (Nordic Society for Pediatric Hematology and Oncology) studies 9 and 33% in 106 patients treated within the French LAME (Leucémie Aiguë Myéloblas-tique Enfant) 89/91 protocol. 3 Data from the St Jude institutional trials showed a 5-year OS of 23% in 160 relapse patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 Allo-SCT in CR2 has been associated with a 5-year OS rate of 62% in recent studies. 9 From 1987 to 2003, a total of 1251 patients with de novo AML were registered in three consecutive protocols of the AML-Berlin/Frankfurt/Muenster study group (AML-BFM-87, AML-BFM-93, AML-BFM-98), of whom 379 patients relapsed between 1987 and 2007. In this study, we analyze the outcome after relapse in this cohort on the basis of the intensity of firstline treatment, including allo-SCT or autologous SCT (auto-SCT), duration of first remission, modalities of relapse treatment and achievement of a second complete remission (CR2).…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6 Recent results from clinical trials indicate a 1-year overall survival (OS) rate of 60 to 70%. [7][8][9] In children with AML who relapsed post-ASCT and after a second ASCT, it was reported at approximately 30 to 40% by Lee et al 9 In 2013, survival outcomes were reported to be similar between adolescents and children with AML following ASCT. 10 Myeloablative preparative regimen used for ASCT induces profound neutropenia and platelet decrease.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of relapse the prospects of cure remain dismal with alternate chemotherapy. [3][4][5] Data from the most recent international BFM relapse show that only 72% of children achieve a second CR. Five-year OS was 32%.…”
Section: Introductionmentioning
confidence: 99%